The influence of employee training and behaviour increase motivation that shapes employee performance - Permata Sari, Winda Khaerunnisa; Sri Wahyuni, Zainal Ilmi, (Jurnal Mirai Management, 2025)
The background of this study is the high number of layoffs and the need to increase the effectiveness of human resource management in the outsourcing sector. This study aims to analyze the effect of training and employee behavior on work motivation and its impact on employee performance at PT Syah Perdana Abadi. This research uses a quantitative method using a survey. The sample in this study amounted to 115 respondents selected by purposive sampling technique. The instrument used was a questionnaire with a Likert scale, and the data was analyzed using the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS). The results showed that training has a positive and significant effect on work motivation, but has no direct effect on performance. Employee behavior is proven to have a positive and significant effect on motivation and performance. Meanwhile, work motivation has a positive and significant effect on performance. Thus, motivation has a mediating role in the relationship between training and behavior to performance. The implications of these findings emphasize the importance of strengthening work motivation and behavior as the key to improving employee performance in a sustainable manner.